Investigations of the role of myomegalin in the phosphorylation of cardiac myosin binding protein C - Uys, Gerrida Mathilda (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biomedical Sciences))--University of Stellenbosch, 2010.